Breast awareness mobile apps for health education and promotion for breast cancer - Yusuf, Azlina; P. Iskandar, Yulita Hanum; Ab Hadi, Imi Sairi; Nasution, Arryana; Lean Keng, Soon (Frontiers in Public Health, 2022)
Background: Lack of knowledge, poor awareness, and attitude are barriers to breast cancer (BC) screening participation. The ubiquitous usage of mobile phones makes it a perfect platform for delivering interventions to increase knowledge and awareness in screening, a strategy for early identification of BC. However, although numerous applications for BC prevention are available on major mobile phone platforms, relatively few have been tested in scientific studies to determine their efficacy. Objective: This study aimed to assess the efficacy of BrAware Apps in increasing the knowledge of BC risk factors, awareness of warning signs and confidence in breast self-examination (BSE) among women in northeast peninsular Malaysia. Methods: A quasi-experimental pre and post-test research design were conducted with 41 women participants in Kelantan, Malaysia, before and after using the BrAware apps. Participants were given an online, adapted Breast Cancer Awareness Measure questionnaire. Post-test was two months after using the BrAware apps. Comparison using paired T-tests were conducted to evaluate the change in knowledge of risk factors, warning signs awareness and confidence level for BSE. Results: The mean age of women was 39.71±8.80. The participants' mean knowledge score of BC warning signs differs before using BrAware (mean 70.62, SD 11.74) and after using the BrAware app (mean 79.83, SD 10.15) at the <0.001 level of significance. Conclusions: The BrAware mobile app had a positive effect in increasing the women's knowledge of risk factors of BC, warning signs awareness and confidence level for BSE. It can be concluded that the mobile app may be an adjunct in educating women on BC.